Democratic Leadership in the Management of Student Discipline in Islamic Boarding Schools - Lalu Iwan Eko Jakandar; Ribut Wahyu Eriyanti; Fauzan Fauzan; Ria Arista (JIE (Journal of Islamic Education), 2024)
This study aims to determine the implementation of democratic leadership in managing student discipline at the Babussalam Islamic Boarding School. The research method used is a qualitative approach with data collection techniques through in-depth interviews, observation and document analysis. The research results show that democratic leadership in Islamic boarding schools facilitates the active participation of students in the decision-making process regarding disciplinary policies. Open discussions, deliberations and participatory meetings provide a forum where students can voice their opinions and ideas. In addition, this research identifies the impact of implementing democratic leadership where students show an increase in compliance with the rules created together. They feel more responsible for their self-discipline and feel valued by the Islamic boarding school environment. However, there are also obstacles, such as differences in interpretations of Islamic values ​​and challenges in maintaining a balance between students' autonomy and collective discipline. Thus, this research makes an essential contribution to understanding the practice of democratic leadership at the Babussalam Islamic boarding school and describes its impact on the character formation and discipline of the students. The implications of the results of this research highlight the importance of maintaining traditional values ​​while introducing a participatory approach that is in line with the demands of the times, creating an educational environment that is inclusive and responsive to the needs of students, and enriching the discourse on Islamic education in Indonesia.